2020
DOI: 10.1186/s40543-020-00241-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential antibiofilm activity of farnesol-loaded poly(DL-lactide-co-glycolide) (PLGA) nanoparticles against Candida albicans

Abstract: Candida species are ubiquitous fungal pathogens and are the most common causes of mucosal and invasive fungal infections in humans. Especially Candida albicans commonly resides as a commensal in the mucosal tissues of approximately half of the human population. When the balance of the normal flora is disrupted or the immune defenses are compromised, Candida species can become pathogenic, often causing recurrent disease in susceptible individuals. The treatments available for Candida infection are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The nanoparticle size substantially impacts the diffusion of Thy-NPs into the biofilm matrix, leading to more damage to the biofilm cells. The nanoparticle's surface charge can be responsible for specific biofilm targeting by electrostatic interactions with the biofilm matrix, favoring the attachment of nanoparticles to the biofilm matrix and resulting in the release of the drug inside the biofilm [ 15 , 30 ]. Additionally, the nanoparticle's high surface-area-to-volume ratio could enable high penetration of the drug, which may result in stronger antibiofilm efficacy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticle size substantially impacts the diffusion of Thy-NPs into the biofilm matrix, leading to more damage to the biofilm cells. The nanoparticle's surface charge can be responsible for specific biofilm targeting by electrostatic interactions with the biofilm matrix, favoring the attachment of nanoparticles to the biofilm matrix and resulting in the release of the drug inside the biofilm [ 15 , 30 ]. Additionally, the nanoparticle's high surface-area-to-volume ratio could enable high penetration of the drug, which may result in stronger antibiofilm efficacy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the antibiofilm activity of CNPs at different concentrations was investigated, in response to P. aeruginosa , S. aureus and C. albicans as representative strains of gram-negative, gram-positive bacteria and eukaryotic biofilm-forming pathogens, respectively. Their pathogenicity was listed tremendously in food intoxication, water-borne diseases and nosocomial infections 96 , 97 . Herein, crystal violet was employed to detect the biofilm inhibition directly on the bottom and inner walls of the microtiter plate.…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that F-PLGA nanoparticles are effective and biocompatible alternatives to inhibit the growth and biofilm formation of C. albicans. 140 In another study, PLGA nanoparticles were studied for antibiotic delivery in periodontitis. Kashi et al developed a new method for producing PLGA nanoparticles containing minocycline, a drug suitable for periodontal infections.…”
Section: ■ Antibioticsmentioning
confidence: 99%
“…Gorso et al used emulsion evaporation method to load farnesol into PLGA nanoparticles (F-PLGA NPs). Their results showed that F-PLGA nanoparticles are effective and biocompatible alternatives to inhibit the growth and biofilm formation of C. albicans . In another study, PLGA nanoparticles were studied for antibiotic delivery in periodontitis.…”
Section: Alternative Antibacterial Agentsmentioning
confidence: 99%